Cybercrime Growth and Law Enforcement Challenges in Indonesia: A Cybercriminology Perspective - Kuswardani Kuswardani; Marisa Kurnianingsih; Andria Luhur Prakosa; Fahmi Fairuzzaman (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study examines the increasing complexity of cybercrime in Indonesia, which is influenced not only by technological development but also by the interaction of individual, structural, and institutional factors in digital environments. The objective is to analyze criminological factors contributing to cybercrime and to examine law enforcement challenges from a cybercriminology perspective in Indonesia. This research uses a normative juridical method with a qualitative approach based on secondary data obtained from legal documents, scientific literature, and previous studies. Data were collected through a systematic literature review and document analysis. The findings show that cybercrime is driven by offender motivation and rationality, technological accessibility, anonymity, and opportunity structures in cyberspace. Law enforcement faces challenges such as difficulties in identifying perpetrators, limited digital forensic capacity, regulatory gaps, and jurisdictional constraints due to the transnational nature of cybercrime. This study contributes to cybercriminology by integrating criminological and legal perspectives into a unified analytical framework for understanding cybercrime as a multidimensional phenomenon. The implication is that effective cybercrime countermeasures require strengthening legal frameworks, institutional capacity, and technological readiness.